The population of Ctenomys from the Ñacuñán Biosphere Reserve (Mendoza, Argentina) belongs to Ctenomys mendocinus Philippi, 1869 (Rodentia: Ctenomyidae): molecular and karyotypic evidence - Parada, Andres; Ojeda, Agustina; Tabeni, Solana; D'elía, Guillermo (Zootaxa, 2012)
Subterranean tuco-tucos of the genus Ctenomys are caviomorph rodents comprising a complex of over 50 nominal speciesfound in the southern half of South America. The validity of several nominal forms awaits a proper assessment. Thepopulation of Ctenomys from Ñacuñán Biosphere Reserve (Mendoza, Argentina) has been classically considered torepresent a distinct species and has been commonly referred as Ctenomys “eremofilus”. Based on molecular andcytogenetic analysis we assessed the taxonomic status of the Ctenomys population of Ñacuñán. Specimens analyzedshowed two very similar chromosome complements (2n=48 and 2n=50), the latter being widely distributed in populationsof C. mendocinus. Similarly, haplotypes recovered from Ñacuñán specimens are very similar and sister to those recoveredfrom specimens of C. mendocinus. Considering this evidence we conclude that the individuals of Ctenomys from Ñacuñán population should be assignable to C. mendocinus.